Kebebasan Hak Memilih Dalam Pemilu 2024 Pada Masyarakat Program Keluarga Harapan ‎Berdasarkan Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum Di Tinjau ‎Dari Perspektif Fiqih Siyasah - Sidik, Erwanda; Sativa, Annisa (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the freedom of voting rights in the 2024 general election among beneficiaries of the Family Hope Program (Program Keluarga Harapan) in light of Law No. 7 of 2017 on General Elections, analyzed through the perspective of fiqh siyasah. Using a normative legal research method with a juridical-normative approach, the study draws upon constitutional and statutory frameworks. The 2024 election, as the world’s largest single-day democratic event, highlights the principle of direct, free, confidential, honest, and fair participation. However, the research is motivated by the erosion of voting freedom among lower-income groups, particularly beneficiaries of the Family Hope Program, who remain vulnerable to systemic money politics. Findings reveal that from the fiqh siyasah perspective, the principles of siyasah dusturiyah emphasize constitutional order, the symbiotic relationship between state and citizens, and the obligation to protect fundamental rights. Strengthening the implementation of Law No. 7 of 2017, with additional provisions ensuring the right to vote for economically disadvantaged groups, is essential to safeguard equality (al-musawah) before law and government. The study concludes that law enforcement and electoral supervision must be reinforced to prevent authoritarian and exploitative practices, ensuring democratic integrity in Indonesia’s electoral process.